The Role of Electronic Administration in Achieving Quality Assurance and Academic Accreditation Standards in Iraqi Public Universities - Shindi, Sanaa; Alsheikh, Ghadah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the role of electronic administration in achieving quality assurance and academic accreditation standards in Iraqi public universities. Five criteria are considered: the institutional context, the quality of teaching and learning, student education support, infrastructure support, and social contributions. The researchers used the descriptive survey approach in their study and a questionnaire as a tool for collecting information. The study is applied to one of the Iraqi government universities. Among the most important results were the following: the study individuals agreed to the importance of electronic administration in achieving quality assurance and academic accreditation standards in the following areas: the field of institutional context, the field of teaching and learning quality, the field of student education support, the field of infrastructure support, and the field of social contributions.